A survey study on use of over the counter (OTC) drugs among medical students, nursing and clerical staff of a tertiary care teaching rural hospital - Parikh, Devang; Sattigeri, B. M.; Kumar, Ashok; Brahmbhatt, Shruti (International Journal of Research in Medical Sciences, 2017)
Aim: The study was conducted to evaluate use of over the counter (OTC) drugs among the medical students, nursing and clerical staff of tertiary care teaching rural hospital to determine the awareness and disadvantages on use of OTC. Methods: Responses to a feedback questionnaire covering various aspects on usage of OTC drugs were obtained from 100 medical students, 100 nursing and 100 clerical staff. Results: Among 300 respondents, 84% used OTC, commonly purchased by self. Majority of them started self medication within 2 days of their illness. The frequently reported illness that prompted self-medication included headache, cough and cold, fever, generalised weakness, acidity, dysmenorrhoea, and sleep disturbances. Majority of them obtained OTC by mentioning name of drug (81%), 35% by telling symptom and 15% by showing old prescription. We found that 87% people share OTC among relatives and friends. Conclusions: Usage of OTC was highest amongst medical students and nursing staff. Time consumption for consultation, the consultation fees and frequent visits were the commonly mentioned reasons for self medication. It was analysed that none of the clerical staff were aware of the drug, dose, frequency of administration and adverse reactions. While very little awareness of medication was found even among nursing staff and medical students. Therefore it is suggested that the public has to be educated on the type of illnesses to be self-diagnosed and medicated, dangers of OTC on misuse which would possibly lead to delay in detection of more serious underlying ailment and timely medication.